Beyond price shocks: Developing resilience indices for measuring EU energy vulnerabilities - Vlachos, Konstantinos; Economou, Maria; Xydis, George (Edelweiss Applied Science and Technology, 2025)
This paper aims to study the effects of geopolitical tensions on the European Union’s oil and natural gas markets from 1990 to 2022. The purpose of this research is to critically assess the impact of geopolitical risks on energy security and market volatility. A literature review is conducted, focusing on tensions between Russia and Ukraine over the past two decades, providing evidence and examples of how geopolitical tensions influence oil and gas markets. No other specific geopolitical events are covered within this paper. The review considers current metrics and the effects of geopolitical risk on the international oil and gas markets. The key findings indicate significant vulnerability; analyzing data from the European Commission and other international organizations, this paper concludes that, although progress has been observed in energy efficiency and renewable energy generation, the EU’s dependence on fossil fuel imports has increased, while domestic production has declined, despite price volatility caused by previous disruptions.